Konsep Pembagian Keuntungan Atas Pendaftaran Ekspresi Budaya Tradisional Terhadap Regulasi Hak Cipta Di Indonesia - Pardosi, Gaudensio Mulagabe; Yuliati (RechtJiva, 2026)
This study arose from a fundamental question regarding the existence of regulations on Traditional Cultural Expressions, which have yet to be comprehensively addressed in Indonesia. Although the relevant provisions are outlined in Article 38 of Law No. 28 of 2014 on Copyright, in practice, law enforcement remains plagued by gaps in legal norms, with no specific figures regarding the benefits to be provided to Indigenous Communities, even though indigenous communities today show a very high level of enthusiasm for registering their Traditional Cultural Expressions, yet there has been no concrete recognition of benefits from the state as a form of economic support for these communities. In this study, the author uses a normative juridical method with a legislative approach and a comparative approach through a literature study. The author also explored primary, secondary, and tertiary legal sources, both offline and online, to find accurate, factual, and comprehensive data. Finally, this research was developed with qualitative analysis and grammatical interpretation to form a concrete research argument. This research has yielded one result, namely that the regulation of Traditional Cultural Expressions in Indonesia requires important components to be embedded in its regulations, such as the concept of Benefit Sharing, which is aligned with the principle of Community-Based Economic Development (CBED) as a test of the viability of indigenous communities themselves. In the future, as a form of legal innovation, there is a need for sui generis regulations in the form of a Traditional Cultural Expression Law (UU EBT), a special regulation that regulates the above concept so that in the future there will be no legal overlap in practice.